Rethinking Human Rights and Peace in Post-Independence Timor-Leste Through Local Perspectives (Book Review) - Kaho, Eventus Ombri (Retorik: Jurnal Ilmu Humaniora, 2025)
Rethinking Human Rights and Peace in Post-Independence Timor-Leste Through Local Perspectives. Khoo, Ying Hooi, Antero Benedito da Silva, and Therese Nguyen Thi Phuong Tam, eds. Singapore: Palgrave Macmillan, 2022.